Molecular phylogeny of holothuria (Mertensiothuria) leucospilota (Brandt 1835) as inferred from cytochrome C oxidase I mitochondrial DNA gene sequences - Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah; Hashim, Ridzwan; Usup, Gires; Ahmad, Hajar Fauzan; Anua, Mohd. Hanafi; Idris, Mohd Yaman (Penerbit UKM, 2011)
Holothuria (Mertensiothuria) leucospilota (Brandt 1835), white threads fish or locally known as bat puntil is currently considered as the most abundant sea cucumber species in Malaysia. This study aimed to generate the genetic profile of H. leucospilota from Malaysia and then to determine the phylogenetic relationship between H. leucospilota and other members of genus Holothuria using partial sequences of cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene. In this study, specimens of H. leucospilota were collected from Intan Besar Island, Langkawi, Kedah Darul Aman in the west coast of Peninsular Malaysia. Three main methods namely neighbour joining, maximum parsimony and maximum likelihood were used for the phylogenetic tree reconstruction. Tree topologies showed that H. leucospilota has its own monophyletic clade clearly distinct from the other species. The pairwise genetic distance calculated further supported these findings. In addition, the results also should that the COI mtDNA gene is capable to unravel the phylogenetic relationship of H. leucospilota.